Factors influencing oral anticoagulant prescribing decisions for patients with atrial fibrillation: a systematic review of qualitative and quantitative evidence. (26th March 2021) - Jarrar, R; Wilkinson, C; Chadwick, T; Lally, J; Thomson, R; Price, C
Abstract: Introduction: Despite their efficacy in reducing stroke risk in patients with atrial fibrillation (AF), oral anticoagulants (OACs) remain under-prescribed [1]. Until recently, warfarin has been the dominant OAC. The introduction of direct oral anticoagulants (DOACs) led to changes in anticoagulant prescribing patterns, with an increase in OAC prescribing and a shift towards DOACs [2]. Treatment decisions for OACs are complicated, and require a discussion between clinicians and patients when deciding on a treatment [1]. Aim: To investigate the main factors that influence initial and ongoing OAC prescribing decisions for patients with AF according to patient and health professional views. Methods: A systematic review was conducted according to the Toolkit for Mixed-Methods Reviews, and was registered on PROSPERO: CRD42019145406. Medline, CINAHL, Scopus, EMBASE, Web of Knowledge and PsychInfo were searched in August, 2019. Primary qualitative and quantitative studies, published between 2009 and 2019, exploring patient and health professional perceptions, views and experiences of OACs in AF were included. McMaster critical appraisal tool for quantitative studies and Critical Appraisal Skills Programme (CASP) checklist for qualitative studies were used for quality assessment. The review followed a convergent integrated approach to data extraction and analysis, which involves extracting and analysing results of quantitative and qualitative studies at the same time using the same method. A data extraction form was adapted from Joanna-Briggs Institute (JBI) mixed-methods extraction form. Study author interpretation of quantitative data was summarised as qualitative statements which were coded together with primary qualitative data using NVIVO 12 software; codes were applied to each sentence in the findings, and were grouped into a hierarchical tree structure Results: The systematic review included 62 papers (58 studies) discussing clinical and non-clinical factors influencing decisions to initiate OACs, the choice between warfarin and DOACs, and the choice between individual OACs. The balance of stroke and bleeding risks was the most influential when making the decision to initiate anticoagulation according to both patients and health professionals. Convenience-related factors, such as monitoring requirements, dosing regimens, and interactions impacted the choice between warfarin and DOACs, whereas, reversibility and dosing regimen influenced the choice between individual medications according to the views of both groups. Health professional specialty and years of experience affected all aspects of treatments, with specialists and senior clinicians more willing to initiate anticoagulation and choose DOACs. Even though health professionals often expressed that patient views were considered when deciding on a treatment, patients generally said that they followed their physician's recommendations without questioning. Conclusion: The review revealed similarities and differences across patient and professional views, experiences, and preferences of anticoagulation. The main discrepancies were related to the decision-making process, and whether patient views are being considered when prescribing. Combining quantitative and qualitative evidence helped explore a wide range of views of OAC and AF, however the review only included published research papers in English, which might have led to exclusion of valuable evidence. More research is needed to explore the factors driving the choice between OACs, especially the choice between individual DOACs. References: 1. Noseworthy PA, Brito JP, Kunneman M, Hargraves IG, Zeballos-Palacios C, Montori VM, Ting HH. Shared decision-making in atrial fibrillation: navigating complex issues in partnership with the patient. Journal of Interventional Cardiac Electrophysiology. 2019;56(2):159–163. 2. Loo, S.Y., Dell'Aniello, S., Huiart, L. and Renoux, C. Trends in the prescription of novel oral anticoagulants in UK primary care. British Journal of Clinical Pharmacology. 2017; 83(9): 2096–2106.